Bicycling renaissance in North America? An update and re-appraisal of cycling trends and policies. - Pucher, John; Buehler, Ralph; Seinen, Mark (My University, 2011)
The article reviews trends in bicycle use, traffic safety and policies to promote and foster cycling in the USA and Canada over the last two decades with a focus on nine large cities (Chicago, Minneapolis, Montréal, New York, Portland, San Francisco, Toronto, Vancouver, and Washington). In general it assesses an increase of bicycle use and a decrease of cyclist fatalities especially in these cities due to a wide range of infrastructure programmes such as the extension and improving of bike lanes, installation of bike sharing systems and bike-transit integration. Furthermore, the article shows that there is a high variation in bicycle use determined by socioeconomic inequality, so that cycling is much more prominent in areas around universities and gentrified parts.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrspolitik; Verkehrssicherheit; Fahrradförderung; Radverkehrsförderung; Fahrradinfrastruktur; Radverkehrsanteil; Fahrradnutzung